Let's get back to the party ebook - Salih, Zak (2021)
“A gorgeously written meditation on being a gay man in America now . . . A raw and captivating debut.” —BookPage Recommended by: O, the Oprah Magazine * BuzzFeed *  The Millions  * Cosmopolitan *  Electric Literature * Literary Hub * Harper's Bazaar * Lambda Literary * LGBTQ Reads * Passport magazine * Paperback Paris * Debutiful * Book Riot * The Bay Area Reporter * The Advocate It is 2015, weeks after the Supreme Court marriage equality ruling. A high school art history teacher, Sebastian Mote envies his queer students and their freedom to live openly the youth he lost to fear and shame. When he runs into his childhood friend Oscar Burnham at a wedding in Washington, DC, he can’t help but see it as a second chance. Now thirty-five, the men haven’t seen each other in more than a decade. But Oscar has no interest in their shared history, nor in the sense of belonging Sebastian craves. Instead, he’s outraged by what he sees as the death of gay culture: bars overrun with bachelorette parties, friends coupling off and having babies. For Oscar, conformity isn’t peace, it’s surrender.   While Oscar and Sebastian struggle to find their place in a rapidly changing world, each is drawn into a cross-generational friendship that treads the line between envy and obsession: Sebastian with one of his students, Oscar with an older icon of the AIDS era. And as they collide again and again, both men must reckon not just with each other but with themselves. Provocative, moving, and rich with sharply drawn characters, Let’s Get Back to the Party introduces an exciting and contemporary new talent.